Reusability of filtering facepiece respirators after decontamination through drying and germicidal UV irradiation - David Vernez; Jonathan Save; Anne Oppliger; Nicolas Concha-Lozano; Nancy B Hopf; Hélène Niculita-Hirzel; Grégory Resch; Véronique Michaud; Laurie Dorange-Pattoret; Nicole Charrière; Kiattisak Batsungnoen; Guillaume Suarez (BMJ Global Health)
Introduction During pandemics, such as the SARS-CoV-2, filtering facepiece respirators plays an essential role in protecting healthcare personnel. The recycling of respirators is possible in case of critical shortage, but it raises the question of the effectiveness of decontamination as well as the performance of the reused respirators.Method Disposable respirators were subjected to ultraviolet germicidal irradiation (UVGI) treatment at single or successive doses of 60 mJ/cm2 after a short drying cycle (30 min, 70°C). The germicidal efficacy of this treatment was tested by spiking respirators with two staphylococcal bacteriophages (vB_HSa_2002 and P66 phages). The respirator performance was investigated by the following parameters: particle penetration (NaCl aerosol, 10–300 nm), scanning electron microscopy (SEM), Fourier-transform infrared spectroscopy (FTIR), differential scanning calorimetry and mechanical tensile tests.Results No viable phage particles were recovered from any of the respirators after decontamination (log reduction in virus titre >3), and no reduction in chemical or physical properties (SEM, particle penetrations <5%–6%) were observed. Increasing the UVGI dose 10-fold led to chemical alterations of the respirator filtration media (FTIR) but did not affect the physical properties (particle penetration), which was unaltered even at 3000 mJ/cm2 (50 cycles). When respirators had been used by healthcare workers and undergone decontamination, they had particle penetration significantly greater than never donned respirators.Conclusion This decontamination procedure is an attractive method for respirators in case of shortages during a SARS pandemic. A successful implementation requires a careful design and particle penetration performance control tests over the successive reuse cycles.